Le temps éclaté : Why Be Happy When You Could Be Normal? De Jeanette Winterson - Jean-Michel Ganteau (Sillages Critiques)
This article reads Why Be Happy When You Could Be Normal? in the light of Oranges Are not the Only Fruit. To do so, it relies on the temporal orientation of trauma theory and tries to demonstrate how Winterson’s oeuvre as a whole is dominated by the workings of afterwardsness, a category that is also obviously at work in Why Be Happy When You Could Be Normal? considered individually. The modalities of temporal inversion inherent in traumatic time are envisaged through the figures of the spiral and the metalepsis. The figures of the spectre and the crypt are then summoned as illustrations of traumatic repetition and temporal fragmentation. The conclusion branches out towards an evocation of traumatic effects and ethical opening.